How to Perform Better on Oxford UKA? A Technical Note from over 500 Surgical Experiences - Peng Zhang; Jiaxiang Bai; Jing Wang; Chen Zhu; Wei Zhou (Orthopaedic Surgery, 2023)
Oxford unicompartmental knee arthroplasty (UKA) has been particularly prevalent because the concept of knee preservation is deeply rooted in people's minds. Mobile bearing UKA is a surgical type of UKA with considerable advantages. This note describes some surgical techniques, including patient position, surgical field exposure, selection of the size of the prosthesis, sagittal tibial osteotomy, placement of the femoral prosthesis and gap balance, to assist surgeons with less experience in performing these operations successfully. The techniques described in this note have been used in over 500 Oxford UKA cases, and nearly 95% patients achieved good prosthesis position and satisfactory postoperative outcome. We hope that the empirical summaries from numerous cases will help surgeons to learn Oxford UKA quickly and effectively, driving the spread of the technique and benefiting more patients.